Early health system responses to the COVID-19 pandemic in Mediterranean countries: A tale of successes and challenges. Issue 5 (May 2022) - Waitzberg, Ruth; Hernández-Quevedo, Cristina; Bernal-Delgado, Enrique; Estupiñán-Romero, Francisco; Angulo-Pueyo, Ester; Theodorou, Mamas; Kantaris, Marios; Charalambous, Chrystala; Gabriel, Elena; Economou, Charalampos; Kaitelidou, Daphne; Konstantakopoulou, Olympia; et al.
Highlights: Speed and adaptive management in health policy responses were key to responding to immediate needs during the COVID-19 pandemic. The approach to governance in the early stages was undertaken centrally in all the Mediterranean countries. Stretched public resources prompted countries to deploy "flexible" intensive care unit (ICU) capacity and workforce as an agile solution. The private sector was also utilized to expand resources and health workforce capacity, through special public-private partnerships. Countries ensured universal coverage for COVID-19-related services, even for groups not usually entitled. Abstract: This paper conducts a comparative review of the (curative) health systems' response taken by Cyprus, Greece, Israel, Italy, Malta, Portugal, and Spain during the first six months of the COVID-19 pandemic. Prior to the COVID-19 pandemic, these Mediterranean countries shared similarities in terms of health system resources, which were low compared to the EU/OECD average. We distill key policy insights regarding the governance tools adopted to manage the pandemic, the means to secure sufficient physical infrastructure and workforce capacity and some financing and coverage aspects. We performed a qualitative analysis of the evidence reported to the 'Health System Response Monitor' platform of the European Observatory by country experts. We found that governance in the early stages of the pandemic was undertaken centrally in all the Mediterranean countries, even in Italy and Spain where regional authorities usually have autonomy over health matters. Stretched public resources prompted countries to deploy "flexible" intensive care unit capacity and health workforce resources as agile solutions. The private sector was also utilized to expand resources and health workforce capacity, through special public-private partnerships. Countries ensured universal coverage for COVID-19-related services, even for groups not usually entitled to free publicly financed health care, such as undocumented migrants. We conclude that flexibility, speed and adaptive management in health policy responses were key to responding to immediate needs during the COVID-19 pandemic. Financial barriers to accessing care as well as potentially higher mortality rates were avoided in most of the countries during the first wave. Yet it is still early to assess to what extent countries were able to maintain essential services without undermining equitable access to high quality care.